Effect of pinch point temperature difference on cost-effective performance of organic Rankine cycle - Li, You-Rong; Wang, Jian-Ning; Du, Mei-Tang; Wu, Shuang-Ying; Liu, Chao; Xu, Jin-Liang (International journal of energy research, 2013)
SUMMARY In this paper, the effect of the pinch point temperature difference (PPTD) in an evaporator and a condenser on the performance of the organic Rankine cycle system has been evaluated for several potential organic working fluids, including R11, R123, R141b, toluene, R114 and n‐pentane, and so on. The net power output per heat transfer area of heat exchangers is used as the objective function in recovering the low grade waste heat of the flue gas released by an industrial boiler. The results indicate that there exists an almost same optimal evaporating PPTD to achieve their respective optimal cost‐effective performance for different organic working fluids under the same condition. With the increase of the total PPTD, the ratio between the evaporating PPTD and the condensing PPTD corresponding to the optimal cost‐effective performance increases. Meanwhile, the evaporating temperature has a little influence on the optimal PPTD assignment. Copyright © 2013 John Wiley & Sons, Ltd.